A Matrix Prediction Model for the 6-Month Mortality Risk in Patients With Anti-Melanoma Differentiation-Associated Protein-5-Positive Dermatomyositis - Ouyang, Zhi-Ming; Lin, Jian-Zi; Tang, Ao-Juan; Yang, Ze-Hong; Yang, Li-Juan; Wei, Xiu-Ning; Li, Qian-Hua; Liang, Jin-Jian; Zheng, Dong-Hui; Guo, Bing-Peng; Zhao, Gui; Han, Qian; et al. (Frontiers in Medicine, 2022)
Objectives The purpose of this study was to investigate the baseline independent risk factors for predicting 6-month mortality of patients with anti-melanoma differentiation-associated gene 5 (anti-MDA5)-positive dermatomyositis (DM) and develop a matrix prediction model formed by these risk factors. Methods The hospitalized patients with DM who completed at least 6-month follow-up were recruited as a derivation cohort. The primary exposure was defined as positive anti-MDA5 at the baseline. The primary outcome was all-cause 6-month mortality after enrollment. A matrix prediction model was developed in the derivation cohort, and another published cohort was used for external validation. Results In derivation cohort, 82 patients with DM were enrolled (mean age of onset 50 ± 11 years and 63% women), with 40 (49%) showing positive anti-MDA5. Gottron sign/papules (OR: 5.135, 95%CI: 1.489–17.708), arthritis (OR: 5.184, 95%CI: 1.455–18.467), interstitial lung disease (OR: 7.034, 95%CI: 1.157–42.785), and higher level of C4 (OR: 1.010, 95%CI: 1.002–1.017) were the independent associators with positive anti-MDA5 in patients with DM. Patients with anti-MDA5-positive DM had significant higher 6-month all-cause mortality than those with anti-MDA5-negative (30 vs. 0%). Among the patients with anti-MDA5-positive DM, compared to the survivors, non-survivors had significantly advanced age of onset (59 ± 6 years vs. 46 ± 9 years), higher rates of fever (75 vs. 18%), positive carcinoma embryonic antigen (CEA, 75 vs. 14%), higher level of ferritin (median 2,858 ug/L vs. 619 ug/L, all p < 0.05). A stepwise multivariate Cox regression showed that ferritin ≥1,250 μg/L (HR: 10.4, 95%CI: 1.8–59.9), fever (HR: 11.2, 95%CI: 2.5–49.9), and positive CEA (HR: 5.2, 95%CI: 1.0–25.7) were the independent risk factors of 6-month mortality. A matrix prediction model was built to stratify patients with anti-MDA5-positive DM into different subgroups with various probabilities of 6-month mortality risk. In an external validation cohort, the observed 6-month all-cause mortality was 78% in high-risk group, 43% in moderate-risk group, and 25% in low-risk group, which shows good accuracy of the model. Conclusion Baseline characteristics such as fever, ferritin ≥1,250 μg/L, and positive CEA are the independent risk factors for 6-month all-cause mortality in patients with anti-MDA5-positive DM. A novel matrix prediction model composed of these three clinical indicators is first proposed to provide a chance for the exploration of individual treatment strategies in anti-MDA5-positive DM subgroups with various probabilities of mortality risk.